Journal of Region, Economy and Society: On the eve of departure - Józsa, László (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
It is gratifying to see that a journal, which I played a major role in founding as dean at the time, is still operating ten years later and provides a scientific forum for those involved in economics, regional studies, and, more broadly, the social sciences. In 2012, Professor János Rechnitzer, then head of the Doctoral School, and I, then dean of the Gyula Kautz Faculty of Economics, discussed the idea of creating the journal. We believed that the time was ripe to create a journal, based on international and domestic examples, with the aim of presenting scientific results in a way that would be backed by our increasingly strong faculty. At that time, the faculty had become one of Hungary’s most renowned economic training institutions, and every year, numerous students completed their dissertations within the framework of the Doctoral School.